PENDEKATAN BUDAYA HUKUM SEBAGAI SUBSISTEM HUKUM DALAM PEMBENTUKAN UNDANG-UNDANG CIPTA KERJA - Deny Susanto (KOLONI, 2022)
The Job Creation Act's ratification offers the most recent rules for labor laws in Indonesia. These guidelines are part of regulatory norms that adapt to legal culture, particularly those pertaining to the community's legal interests, which are covered by the labor law sector. The study methodology employed is normative research, which involves keeping an eye on the Employment Creation Act's regulations, related employment discussions, and labor laws before they are changed. This study aims to evaluate the applicability of taking legal cultural factors into account when creating relevant laws and regulations. The results of this study indicate that the consideration of legal cultural issues has not been ideal in the development of connected legislation, and as a result. Keywords: Cipta Kerja Act, Culture Law, Labour